Fixed supports and realistic blast studies - Del Linz, Paolo (Nanyang Technological University, 2020)
Real design scenarios are likely to differ in several respects from the analysed situations. One of these is the boundary condition. In the cases considered previously, the slabs were always simulated as simply supported, since this was the condition generally used during the tests. In realistic structures it is more likely that the concrete elements will have fixed boundary conditions, as these better represent the reinforcement ties generally included in design. Additionally, lower stand-offs and more concentrated fragment distributions are also likely to be required when design conditions are determined. Therefore, it was decided that the ability of modelling such different situations was an important parameter to assess the capability of the modelling method developed.